"You Never Know Who's Looking at Your Page!": African American Male Adolescents' Perceptions of Emotional Display Rules Online. (21st February 2019) - Galletta Horner, Christy; Akiva, Thomas
Abstract : Social network sites (SNSs) are a powerful new context for adolescent development. We qualitatively investigate African American adolescent boys' ( N  = 50, mean age = 15.8) perceptions of emotional display rules on SNSs. We present and discuss a taxonomy of display rules for anger, sadness, embarrassment, and excitement. Perceived display rules around anger and sadness were most notable. Participants' understandings of display rules around anger were complex and varied, with many describing threats of violence as marking the line between acceptable and unacceptable expressions. Although youth stated that expressing sadness via SNS could garner emotional support, this was understood somewhat consistently as unacceptable. Overall, our findings suggest that perceptions of emotional display rules on SNSs are varied, complicated, and can be difficult to navigate.